Bayesian Estimating for cox Ingersoll Ross process - Reyam abo-alhell; Muhannad F. Al Saadony (Al-Qadisiyah Journal of Pure Science, 2021)
the model of term structure of interest rates are consider the most significant and computationally difficult portion of the modern finance due to a relative complexity of using techniques. This article concerns the Bayesian estimation of interest rate models. Assume the short term interest rate follows the Cox Ingersoll Ross (CIR) process , this process has several feature. In particular mean reverting and the other feature is remanis non- negative , so this is what distinguishes it from previous models. It is implement in the R programing.